(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study explores the performance and innovative work behavior of employees at the National University of Timor Leste (UNTL). The aim of this study is to analyze the factors influencing these behaviors and provides recommendations for fostering a more innovative work environment. This study employed a qualitative approach with data gathering through in-depth interviews with a diverse group of university employees. The study reveals that organizational support and individual motivation are the factors can affect employee performance and innovation. The findings suggest that strategic interventions at both organizational and individual levels are essential to enhance performance and innovation at UNTL.